Reliability-Based Analysis of Main Propulsion Fuel Oil System Maintenance for Tugboats with Qualitative and Quantitative Methods - Imam Pujo Pujo Mulyatno; Keyza Taqi Wafi; Sarjito Jokosisworo; Tuswan Tuswan (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2023)
This study aims to analyze the maintenance of the main propulsion fuel oil system for tugboats using both qualitative and quantitative methods. The focus is on evaluating the reliability of the system and identifying potential areas for improvement. The research employs a combination of expert interviews, industry standards, and statistical analysis to provide a comprehensive overview of the maintenance practices in place. The goal is to enhance the overall performance and longevity of the main propulsion fuel oil system in tugboats. The study uses data on the operational time, failure time and frequency, the number of vessels served, and fuel system diagrams to analyze the system's reliability. Qualitative methods such as Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA) were used, as well as quantitative methods such as Overall Equipment Effectiveness (OEE), Markovian Decision Process (MDP), and reliability methods. The study found that the FO Purifier component was the critical component with a Risk Priority Number (RPN) of 294. The average value of OEE was 47%, lower than the standard of 85%. The MDP analysis showed a probability of 0.08 for mild damage and 0.46 for moderate to severe damage under steady-state conditions. The FO Purifier component had the lowest Mean Time to Failure (MTTF) value of 1658.50 hours. The study provides a graph of the reliability function against time, and recommends maintenance actions based on the MTTF and MDP.